2021
DOI: 10.11648/j.epes.20211001.11
|View full text |Cite
|
Sign up to set email alerts
|

Solar Photovoltaic Systems on Public Schools Buildings: A Case Study in Palestine

Abstract: Renewable energy exploitation has proved its promising characteristics in sustainably securing energy needs. This work is a comprehensive assessment of the potential of renewable penetration in securing electricity needs in Palestine. Methods of assessment have been determined based on solar potential. Al-Dahriya secondary school in the south Hebron directorate of education was used as a case study, where these building have low working hours all over the year, which will increase the total income of the annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…-Masrur et al [6] analyzed techno-economic evaluations like net present value (NPC) levelized cost of energy (LOCE) for optimally tilted PV system located at Hatiya, Bangladesh, and concluded that the power exchange cost is lower than the value of the derating factor. -Alsamamra and Shoqeir [7] using HOMER Pro software simulation of a 57.16 kW rooftop PV system with 144 panels and concluded that due to low working hours and less energy consumption the payback period is 4.38 years. -Yadav and Bajpai [8] analyzed the performance analysis of a 5 kW rooftop solar plant in northern parts of India has an annual average reference yield of 5.23 kWh/kW/day, array yield of 4.51 kWh/kW/day and final yield of 3.99 kWh/kW/day.…”
Section: Introductionmentioning
confidence: 99%
“…-Masrur et al [6] analyzed techno-economic evaluations like net present value (NPC) levelized cost of energy (LOCE) for optimally tilted PV system located at Hatiya, Bangladesh, and concluded that the power exchange cost is lower than the value of the derating factor. -Alsamamra and Shoqeir [7] using HOMER Pro software simulation of a 57.16 kW rooftop PV system with 144 panels and concluded that due to low working hours and less energy consumption the payback period is 4.38 years. -Yadav and Bajpai [8] analyzed the performance analysis of a 5 kW rooftop solar plant in northern parts of India has an annual average reference yield of 5.23 kWh/kW/day, array yield of 4.51 kWh/kW/day and final yield of 3.99 kWh/kW/day.…”
Section: Introductionmentioning
confidence: 99%
“…The installation of PV systems on the school buildings rooftop in Palestine proved to be economically encouraging with a payback period of fewer than 5 years, besides its environmental and increasing energy security benefits [31]. A study by Alsamamra and Shoqeir found that installing PV systems on the rooftop in all the schools in Palestine can provide around 5% of the total annual energy consumption in Palestine [32]. Besides, the school buildings provide a potential environment for investment in PV systems due to the larger roof area for each building, and the limited use of electricity in schools compared to the residential buildings.…”
Section: Introductionmentioning
confidence: 99%